Sistem Pendukung Keputusan Untuk Menentukan Penerima Bantuan Permodalan UMKM Menerapkan Metode SMART - Arif Setiawan; Mesran (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2022)
Determining recipients of MSME capital assistance at the Deli Serdang Regency UKM Cooperative Service is an activity that requires careful assessment and must also be selective based on existing assessments. With this, it is hoped that results can be obtained that are worthy of obtaining business development assistance for Micro, Small and Medium Enterprises (MSMEs) to obtain assistance funds for developing their businesses. The solution to the problem above is to build a Decision Support System to assist in determining the suitability of recipients of MSME capital assistance at the Deli Serdang Regency UKM Cooperative Service. The method chosen to support solving the problem above is the Simple Multi Attribute Rating Technique (SMART) method, namely by giving weight to each available alternative option. This research produces a Decision Support System that can recommend providing assistance to recipients of MSME capital assistance at the Deli Serdang Regency UKM Cooperative Service using the SMART method. A trial was carried out by entering data samples of 7 potential recipients of MSME capital assistance. With the Decision Support System, it can provide recommendations to determine recipients of MSME capital assistance based on ranking, from 7 potential participants receiving MSME capital assistance based on the smallest rank, namely: Sri Rahayu (A1) with a score of 148.97, Putri Handayani (A4) with a score of 148, 99, and Nur Azhari (A3) with a score of 149.76.